Altered membrane properties but unchanged intrinsic excitability and spontaneous postsynaptic currents in an aged APPswe/PS1dE9 model of Alzheimer’s disease - Ohline, Shane M.; Liu, Xinhuai; Ibrahim, Mohamed F.; Mockett, Bruce M.; Empson, Ruth M.; Abraham, Wickliffe C.; Iremonger, Karl J.; Jones, Peter P. (Frontiers in Cellular Neuroscience, 2022)
Neuronal hyperexcitability in Alzheimer’s disease (AD) models is thought to either contribute to the formation of amyloid beta plaques or result from their formation. Neuronal hyperexcitability has been shown in the cerebral cortex of the widely used young APPswe/PS1dE9 mice, which have accelerated plaque formation. However, it is currently unclear if hyperexcitability also occurs in CA1 hippocampal neurons of aged animals in this model. In the present work, we have compared intrinsic excitability and spontaneous synaptic inputs from CA1 pyramidal cells of 8-month-old APPswe/PS1dE9 and wildtype control mice. We find no change in intrinsic excitability or spontaneous postsynaptic currents between groups. We did, however, find a reduced input resistance and an increase in hyperpolarization-activated sag current. These results are consistent with findings from other aged AD model mice, including the widely used 5 x FAD and 3 x Tg. Together these results suggest that neuronal hyperexcitability is not a consistent feature of all AD mouse models, particularly at advanced ages.